2014
DOI: 10.2147/ijnrd.s61895
|View full text |Cite
|
Sign up to set email alerts
|

Switch from epoetin to darbepoetin alfa in hemodialysis: dose equivalence and hemoglobin stability

Abstract: AimThe objective of the study reported here was to describe dose equivalence and hemoglobin (Hb) stability in a cohort of unselected hemodialysis patients who were switched simultaneously from epoetin alfa to darbepoetin alfa.MethodsThis was a multicenter, observational, retrospective study in patients aged ≥18 years who switched from intravenous (IV) epoetin alfa to IV darbepoetin alfa in October 2007 (Month 0) and continued on hemodialysis for at least 24 months. The dose was adjusted to maintain Hb within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this context, it is of utmost importance to underline that none of the studies conducted performed a direct comparison among different switching groups. In particular, three of these studies showed conflicting results in terms of the doses of ESA α that were required to control anaemia in CKD patients switching from originator to biosimilar [2931].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is of utmost importance to underline that none of the studies conducted performed a direct comparison among different switching groups. In particular, three of these studies showed conflicting results in terms of the doses of ESA α that were required to control anaemia in CKD patients switching from originator to biosimilar [2931].…”
Section: Discussionmentioning
confidence: 99%
“…al. [51] HD patients Switch from EPO to DPO resulted in a consistent and substantial 65% reduction in the required dose (p < 0.0001).…”
Section: Arrieta Etmentioning
confidence: 92%
“…Dose equivalence was calculated due to the fact that the patients were using different EPO forms. Conversion from epoetin alfa dose to darbopoetin alfa dose was calculated with a conversion ratio of 300:1 for patients receiving epoetin alfa (≤200 IU/kg/week), while a 350:1 ratio was used for patients receiving higher doses [5].…”
Section: Methodsmentioning
confidence: 99%